Strategies for Sustainable Production of Hydrogen Peroxide via Oxygen Reduction Reaction: From Catalyst Design to Device Setup - Tian, Yuhui; Deng, Daijie; Xu, Li; Li, Meng; Chen, Hao; Wu, Zhenzhen; Zhang, Shanqing (Nano-Micro Letters, 2023)
An environmentally benign, sustainable, and cost-effective supply of H2O2 as a rapidly expanding consumption raw material is highly desired for chemical industries, medical treatment, and household disinfection. The electrocatalytic production route via electrochemical oxygen reduction reaction (ORR) offers a sustainable avenue for the on-site production of H2O2 from O2 and H2O. The most crucial and innovative part of such technology lies in the availability of suitable electrocatalysts that promote two-electron (2e–) ORR. In recent years, tremendous progress has been achieved in designing efficient, robust, and cost-effective catalyst materials, including noble metals and their alloys, metal-free carbon-based materials, single-atom catalysts, and molecular catalysts. Meanwhile, innovative cell designs have significantly advanced electrochemical applications at the industrial level. This review summarizes fundamental basics and recent advances in H2O2 production via 2e–-ORR, including catalyst design, mechanistic explorations, theoretical computations, experimental evaluations, and electrochemical cell designs. Perspectives on addressing remaining challenges are also presented with an emphasis on the large-scale synthesis of H2O2 via the electrochemical route. Highlights: 1 The state-of-the-art development in electrochemical H2O2 production via the two-electron oxygen reduction reaction is reviewed with emphasis on material science, reaction mechanisms, and fundamental factors that govern the reaction route. 2 General principles and strategies for catalyst design are summarized to understand the inherent relationships between the catalyst properties and electrocatalytic performances. 3 Perspectives and challenges are presented to get insights into the large-scale manufacturing of H2O2 via the electrochemical routes.